Prevalence of venous thromboembolism in admissions and readmissions with and without syncope: A nationwide cohort study - Kadri, Amer N. (2021)
Aims: The Pulmonary Embolism in Syncope Italian Trial reported 17.3% prevalence of pulmonary embolism (PE) in patients admitted with syncope. We investigated the prevalence of venous thromboembolism [VTE, including PE and deep vein thrombosis (DVT)] in syncope vs. non-syncope admissions and readmissions, and if syncope is an independent predictor of VTE. Methods and results: We conducted an observational study of index admissions of the 2013-14 Nationwide Readmission Database.